Effect of PEEP and tidal volume on ventilation distribution and end-expiratory lung volume: a prospective experimental animal and pilot clinical study. - Günther Zick (Public Library of Science (PLoS), 2013)
Introduction Lung-protective ventilation aims at using low tidal volumes (VT) at optimum positive end-expiratory pressures (PEEP). Optimum PEEP should recruit atelectatic lung regions and avoid tidal recruitment and end-inspiratory overinflation. We examined the effect of VT and PEEP on ventilation distribution, regional respiratory system compliance (C(RS)), and end-expiratory lung volume (EELV) in an animal model of acute lung injury (ALI) and patients with ARDS by using electrical impedance tomography (EIT) with the aim to assess tidal recruitment and overinflation. Methods EIT examinations were performed in 10 anaesthetized pigs with normal lungs ventilated at 5 and 10 ml/kg body weight VT and 5 cmH2O PEEP. After ALI induction, 10 ml/kg VT and 10 cmH2O PEEP were applied. Afterwards, PEEP was set according to the pressure-volume curve. Animals were randomized to either low or high VT ventilation changed after 30 minutes in a crossover design. Ventilation distribution, regional C(RS) and changes in EELV were analyzed. The same measures were determined in five ARDS patients examined during low and high VT ventilation (6 and 10 (8) ml/kg) at three PEEP levels. Results In healthy animals, high compared to low VT increased C(RS) and ventilation in dependent lung regions implying tidal recruitment. ALI reduced C(RS) and EELV in all regions without changing ventilation distribution. Pressure-volume curve-derived PEEP of 21±4 cmH2O (mean±SD) resulted in comparable increase in C(RS) in dependent and decrease in non-dependent regions at both VT. This implied that tidal recruitment was avoided but end-inspiratory overinflation was present irrespective of VT. In patients, regional C(RS) differences between low and high VT revealed high degree of tidal recruitment and low overinflation at 3±1 cmH2O PEEP. Tidal recruitment decreased at 10±1 cmH2O and was further reduced at 15±2 cmH(2)O PEEP. Conclusions Tidal recruitment and end-inspiratory overinflation can be assessed by EIT-based analysis of regional C(RS).